2016
DOI: 10.1080/07315724.2016.1152928
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Egg Consumption and Risk of Coronary Heart Disease and Stroke

Abstract: The possible relationship between dietary cholesterol and cardiac outcomes has been scrutinized for decades. However, recent reviews of the literature have suggested that dietary cholesterol is not a nutrient of concern. Thus, we conducted a meta-analysis of egg intake (a significant contributor to dietary cholesterol) and risk of coronary heart disease (CHD) and stroke. A comprehensive literature search was conducted through August 2015 to identify prospective cohort studies that reported risk estimates for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(111 citation statements)
references
References 36 publications
4
100
0
7
Order By: Relevance
“…In our study, participants who had the lowest risk of CVD consumed an average of 0.76 egg daily, lower than the highest level in the Western and Japanese population 3. But this average level was close to the amount (40 – 50  g   per day) recommended by the Chinese Dietary Guideline 4.…”
supporting
confidence: 45%
“…In our study, participants who had the lowest risk of CVD consumed an average of 0.76 egg daily, lower than the highest level in the Western and Japanese population 3. But this average level was close to the amount (40 – 50  g   per day) recommended by the Chinese Dietary Guideline 4.…”
supporting
confidence: 45%
“…Therefore, people tend to limit their consumption of eggs to decrease the cholesterol intake, in order to protect themselves from CVD. However, the controversy does not stop here, later studies do not support this hypothesis, and potential beneficial effects of egg on CVD have been reported [1223, 150, 151, 185]. A prospective study with over 117,000 adults and 14-year follow-up demonstrated that there were no differences of CVD risks between participants that consumed one egg per week and those who consumed one egg per day [12].…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%
“…The effects of egg intake on blood cholesterol and CVD have been discussed in several meta-analysis studies using research data collected over 60 years [15, 2123, 180, 194]. Large epidemiological works have been conducted to investigate the effect of egg intake on blood cholesterol levels and risk of CVD in children [123], young people [16, 20, 47, 124], women [1214, 125, 195, 196], men [1214, 125, 195199], and older adults [1214, 125, 195200].…”
Section: The Relationship Between Egg Intake and Cvd Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, cada vez hay más evidencias de que el consumo de huevo tiene poca o nula influencia sobre los niveles de colesterol sérico, mientras que puede incluso ser beneficioso desde el punto cardiovascular. Recientes estudios concluyen que el consumo de huevo no se asocia a un mayor riesgo de enfermedad coronaria (13,14), y no supone un mayor riesgo de ictus (13) e incluso puede ser un factor protector (14).…”
Section: Grasas Del Huevounclassified